2013
DOI: 10.1017/s0022215112003039
|View full text |Cite
|
Sign up to set email alerts
|

Reduction osteoplasty for treating pneumosinus dilatans of the maxillary sinus

Abstract: As pneumosinus dilatans of the maxillary sinus is uncommon, there is no established surgical treatment protocol. This surgical technique was less invasive than other described procedures and revealed good cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…1 The material is also applied in nasal tip surgery, reconstruction of the paranasal sinuses, and reconstruction of the nasal dorsum. [8][9][10] There are several reasons why this material has achieved a moderate degree of popularity in Asian rhinoplasty, including a good safety profile, ease of manipulation, and its ability to provide a smooth postoperative contour of the nasal dorsum. Above all, safety is the most significant factor that distinguishes TPFL from commonly used alloplastics.…”
Section: Discussionmentioning
confidence: 99%
“…1 The material is also applied in nasal tip surgery, reconstruction of the paranasal sinuses, and reconstruction of the nasal dorsum. [8][9][10] There are several reasons why this material has achieved a moderate degree of popularity in Asian rhinoplasty, including a good safety profile, ease of manipulation, and its ability to provide a smooth postoperative contour of the nasal dorsum. Above all, safety is the most significant factor that distinguishes TPFL from commonly used alloplastics.…”
Section: Discussionmentioning
confidence: 99%
“…However, although a nasoantral window may relieve symptoms (if present), deformities may still persist. 14,20,32 Hyun et al 14 reported good cosmetic results after reduction osteoplasty. Antral wall turnover, greenstick downward fracture, and electrical burring were proposed by Choi et al 16 to correct facial deformities based on the thickness of the antral wall and the extension of the expanded area.…”
Section: Managementmentioning
confidence: 99%